2013
DOI: 10.1038/ismej.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose/2-sulfotrehalose biosynthesis and glycine-betaine uptake are widely spread mechanisms for osmoadaptation in the Halobacteriales

Abstract: We investigated the mechanisms of osmoadaptation in the order Halobacteriales, with special emphasis on Haladaptatus paucihalophilus, known for its ability to survive in low salinities. H. paucihalophilus genome contained genes for trehalose synthesis (trehalose-6-phosphate synthase/trehalose-6-phosphatase (OtsAB pathway) and trehalose glycosyl-transferring synthase pathway), as well as for glycine betaine uptake (BCCT family of secondary transporters and QAT family of ABC transporters). H. paucihalophilus cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 56 publications
6
93
0
Order By: Relevance
“…Our previous study (37) has provided experimental and genomic evidence that multiple Halobacteria genera are capable of trehalose or 2-sulfotrehalose biosynthesis as an osmoadaptive strategy and that the otsAB operon (encoding trehalose-6-phosphate synthase/trehalose-6-phosphatase) mediates trehalose biosynthesis in the Halobacteria. Further, analysis of the occurrence patterns of otsAB genes demonstrates a distinct phylogenetic pattern, where the otsAB operon was identified in all members of Halobacteria clade I (as defined in references 42 and 43), as well as in the genera Halococcus, Haladaptatus, Halalkalicoccus, and Halosimplex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study (37) has provided experimental and genomic evidence that multiple Halobacteria genera are capable of trehalose or 2-sulfotrehalose biosynthesis as an osmoadaptive strategy and that the otsAB operon (encoding trehalose-6-phosphate synthase/trehalose-6-phosphatase) mediates trehalose biosynthesis in the Halobacteria. Further, analysis of the occurrence patterns of otsAB genes demonstrates a distinct phylogenetic pattern, where the otsAB operon was identified in all members of Halobacteria clade I (as defined in references 42 and 43), as well as in the genera Halococcus, Haladaptatus, Halalkalicoccus, and Halosimplex.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to salting in, some members of the Halobacteria maintain high intracellular osmotic pressure by synthesis and/or uptake of highly soluble organic solutes that do not interfere with intracellular enzymatic activities and cellular processes. We have recently demonstrated that multiple genera within the Halobacteria biosynthesize and accumulate molar levels of trehalose (or 2-sulfotrehalose) as an osmoadaptive compatible solute (37). Currently, the impact of the possession (or lack thereof) of such a capability within members of the Halobacteria on their ecological fitness, habitat preferences, and, consequently, the overall Halobacteria community structure within a specific saline or hypersaline habitat is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to notice the different alterations of TMAO from trehalose as well, for which a reasonable explanation could be that strain YYL has multiple compatible solute systems in response to different stresses. The presence of different osmoadaptation mechanisms was also found in the Halobacteriales (55). A bacterium could also asymmetrically respond to different stresses (56).…”
Section: Discussionmentioning
confidence: 84%
“…Compatible solution including proline, glutamate, carnitine, betaine, glycine, ectoine, and exotic compatible solutes as 2-sulfotrehalose [51,52].In environmental isotonic,the accumulation of salts like KCl or NaCl are in equal concentrations. As a results, the concentration of high salts have been copied by halophilic proteins (e.g.…”
Section: +mentioning
confidence: 99%